Análise das variáveis meteorológicas no clima urbano de Ourinhos-SP - Bento, Ana Claudia [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Urban Climatology acquires importance in the development and urban planning of cities, since it must occur integration between social and economic development, so that there is an uncontrolled exploitation of natural resources in cities, which are essential to people's lives. Thus, this project aims to understand, analyze, monitor and characterize the urban climate of Ourinhos through the meteorological variables and so understand how occurs comfort / thermal discomfort through the influence on thermal sensation of the population and relate to climatic factors, as is extremely important to contribute to a better quality of life. Ourinhos is a city that is inner, in the southwestern state of São Paulo, bordering the north of Paraná state. This municipality focuses an economy predominantly in trade, cane cultivation of sugar, soy and corn

A Climatologia Urbana adquire uma importância no desenvolvimento e no planejamento urbano das cidades, já que deve ocorrer uma integração entre o desenvolvimento social e econômico, para que não ocorra uma exploração descontrolada nos recursos naturais das cidades, que são essenciais para vida das pessoas. Sendo assim esse projeto tem por objetivo entender, analisar, monitorar e caracterizar o clima urbano de Ourinhos através das variáveis meteorológicas e assim compreender como ocorre o conforto/desconforto térmico através da influência na sensação térmica da população e relacionar aos fatores climáticos, pois é de extrema importância contribuir para uma melhor qualidade de vida das pessoas. Ourinhos é uma cidade que se encontra no interior, no sudoeste do estado de São Paulo, divisa com o norte do estado do Paraná. Seu município concentra uma economia predominantemente no comércio, cultivo de cana de açúcar, soja e do milho
Keywords: Meteorologia; Precipitação (Meteorologia) - Variabilidade; Ourinhos (SP) - Clima